Pelatihan Penyelenggaraan Jenazah dengan Metode Demonstrasi bagi Ibu-ibu Anggota Persatuan Majelis Taklim (Permata) 5 Kelurahan Sialangmunggu Kecamatan Tuah Madani Kota Pekanbaru - Zuraidah, Zuraidah; Irdamisraini, Irdamisraini (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity was motivated by the low level of knowledge and skills among the community, especially women's religious study groups, in conducting funeral rites. Many people consider funeral rites to be a fardhu kifayah (collective obligation) that only needs to be performed by some people, so these skills are not widely possessed. This activity aims to increase participants' knowledge and understanding of funeral procedures through a demonstration method combined with role play, discussion, and audio-visual media. The training was held at the Al-Mujahadah Mosque, Sialangmunggu Village, with 63 participants consisting of women who are members of the majelis taklim. Evaluation was carried out through pre-tests, post-tests, and hands-on practice. The results of the activity showed that the demonstration method was very effective in improving participants' understanding and skills related to funeral practices. Participants were able to independently practice bathing, shrouding, and praying for the deceased. This activity also fostered participants' confidence and social responsibility to be directly involved in funeral arrangements in their respective neighborhoods.